1980
DOI: 10.1021/bi00555a047
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme binding site of glutamate decarboxylase

Abstract: Dissociation constants have been measured for the binding of a variety of simple analogues of pyridoxal 5'-phosphate to apoglutamate decarboxylase. Compounds studied have a simple alkyl or aryl group and a negatively charged substituent (phosphate, phosphonate, phosphoramidate, sulfate, sulfonate, or carboxylate). Optimum binding to the phosphate binding site of the enzyme is achieved by compounds having a double negative charge and a tetrahedral geometry. Planar anions and monoanions bind considerably less we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1982
1982
2002
2002

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…For example, aspartate aminotransferase is converted from an inactive 430 nm‐absorbing protonated internal aldimine to an active unprotonated 362 nm‐absorbing form with a p K of 6.2 in a process that fits well to the ionization of a single proton [30]. It has been suggested that in wild‐type Gad, the ionization responsible for the absorbance change does not take place on the internal aldimine and much evidence indicates that the change in spectrum of the wild‐type enzyme is due to a conformational transition in the protein induced by shifting the pH [31]. It seems very likely that the pH‐dependent changes that occur in the spectrum of the mutants under investigation in the present work are due to the same pH‐induced conformational transition observed in the wild‐type and that the different forms of the cofactor present in wild‐type and mutant enzymes are recording the same event at the active site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, aspartate aminotransferase is converted from an inactive 430 nm‐absorbing protonated internal aldimine to an active unprotonated 362 nm‐absorbing form with a p K of 6.2 in a process that fits well to the ionization of a single proton [30]. It has been suggested that in wild‐type Gad, the ionization responsible for the absorbance change does not take place on the internal aldimine and much evidence indicates that the change in spectrum of the wild‐type enzyme is due to a conformational transition in the protein induced by shifting the pH [31]. It seems very likely that the pH‐dependent changes that occur in the spectrum of the mutants under investigation in the present work are due to the same pH‐induced conformational transition observed in the wild‐type and that the different forms of the cofactor present in wild‐type and mutant enzymes are recording the same event at the active site.…”
Section: Discussionmentioning
confidence: 99%
“…To explain the pH‐dependent occurrence of the 330 nm‐absorbing chromophore, it has been proposed that, in the wild‐type enzyme, high pH induces the formation of an aldamine between the internal aldimine and an enzyme cysteine residue and that the low pH conformation favors the unsubstituted internal aldimine [31]. However, because in the mutant enzymes the high pH favors the 388 nm‐absorbing unsubstituted aldehyde, formation of a covalent bond between PLP and a cysteine side‐chain can be excluded as the basis of the pH‐dependent absorbance changes observed with the Lys276 mutant enzymes.…”
Section: Discussionmentioning
confidence: 99%